A stem anatomical investigation of Cuscuta L. (Convolvulaceae) species in Khorassan provinces - Jamil Vaezi; Zahra Ranjbar; Hamid Ejtahadi; Farshid Memariani (تاکسونومی و بیوسیستماتیک, 2014)
Cuscuta is a common plant parasite and is able to attack several host species. Its haustoria could be penetrated into the phloem of host plant. In this study, the stem anatomy of six species and two varieties of Cuscuta (Cuscuta campestris, C. monogyna, C. brevistyla, C. kotschyana, C. epithymum, C. pedicellata, C. lehmanniana var. lehmanniana and C. babylonica var. babylonica) distributed in Khorassan provinces were investigated using the blue toluidine staining. Cross sections were provided by hand. Results showed that anatomical characters including stem diameter, position and distribution of vessels, number and size of vessels and number of parenchymatous layers were effective traits to taxonomically separate the species under study. Furthermore, the anatomical relationship between parasite and its host plant was examined.